THE IMPACT OF INTELLECTUAL CAPITAL ON THE FIRM PERFORMANCE AND INVESTOR RESPONSE: AN EMPIRICAL STUDY OF SELECTED SECTORS IN COLOMBO STOCK EXCHANGE - Kehelwalatenna, Sampath; Gunaratne, P.S.M. (My University, 2010)
Intellectual capital (IC) is recognized as a strategic asset which gives competitive advantages by driving organizations for superior performance in the modern day knowledge-based economies. The purpose of this study is to investigate, empirically, the relation between IC, and firm performance and the response of investors. In this respect, the study has been conducted using data drawn for 2002 to 2006 from listed financial services and manufacturing sector firms in Sri Lanka. The Pulic’s Value Added Intellectual Coefficient (VAIC) has been employed to measure the IC together with the measurements of value creation efficiencies of capital employed, human capital, and structural capital of selected firms. The researchers use the Pearson’s correlation analysis and construct regression models to investigate the said relationships. Results of the main analysis show that IC is positively associated with firm performance, and investor response. In addition, it is found that the level of importance placed by investors on three components of value creation efficiencies (physical capital, human capital, and structural capital) has not been uniform. Moreover, the results of the extended analyses further confirm some of the above associations with few exceptions. The study is novel and original in its approach to determine the value addition in the VAIC model. In this regard, current study brings the assumptions of the stewardship theory in alternative to both economic value addition and value addition according to the stakeholder theory. Moreover, the results may extend in understanding the role of IC in creating corporate value and building sustainable advantages for companies in developing countries as the findings in developed economies and emerging economies cannot be generalized to developing nations, since country-specific factors and technological advancements influence significantly in determining the level of IC.